EDITORIAL - Palhano Ricarte Oliveira, Angelo; Rocha Machado, Bianca; Campo Dall’Orto Corrêa, Elisa; Carreiro Cruz, Francisco Edson; da Rocha Pacheco, Lauro Vinícius; Möller, Mathias Alberto; Rossineti Rufinoni, Priscila (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2015)
Editorial do volume 04, número 07, ano 2015.